2020
DOI: 10.3390/nu12020482
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an 8 Week Prescribed Exercise and Low-Carbohydrate Diet on Cardiorespiratory Fitness, Body Composition and Cardiometabolic Risk Factors in Obese Individuals: A Randomised Controlled Trial

Abstract: Background: Low-carbohydrate (LC) diets are an effective method for treating obesity and reducing cardiometabolic risk. However, exposure to LC diets is associated with reductions in muscle mass and increased osteoporosis risk in obese individuals. The combination of exercise with a LC diet appears to attenuate muscle mass loss induced by LC diets alone, and to further improve cardiometabolic profile. However, evidence to date in obese individuals is limited. We assessed the effect of LC diet in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 59 publications
3
31
0
Order By: Relevance
“…In some of the trials, isocaloric [ 24 ] or hypocaloric ketogenic diet [ 25 ] did not significantly change lean body mass while reducing body fat. On the contrary and in agreement with our current data, Perissious and colleagues found a reduction in lean body mass in patients with obesity undergoing exercise program while being on low carbohydrate diet [ 26 ]. Differential effect of ketogenic vs. nutritionally balanced diet under hyperenergetic conditions has also been described in a study in healthy men undergoing an eight-week resistance training program.…”
Section: Discussionsupporting
confidence: 93%
“…In some of the trials, isocaloric [ 24 ] or hypocaloric ketogenic diet [ 25 ] did not significantly change lean body mass while reducing body fat. On the contrary and in agreement with our current data, Perissious and colleagues found a reduction in lean body mass in patients with obesity undergoing exercise program while being on low carbohydrate diet [ 26 ]. Differential effect of ketogenic vs. nutritionally balanced diet under hyperenergetic conditions has also been described in a study in healthy men undergoing an eight-week resistance training program.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding VAT, the majority of the published researches on KD and VAT were on persons with obesity [68][69][70][71][72][73], whilst only one previous study investigate the effect of KD on VAT in trained males [21]. Our data confirm the KD exerts a positive effect on VAT not only in persons with obesity but also in athletes.…”
Section: Discussionsupporting
confidence: 72%
“…The titles and abstracts from the initial screening were reviewed and 3007 studies, which were review studies, pilot studies, or not related to this meta-analysis, were excluded. Full texts of the remaining 38 studies were reviewed to determine eligibility, and finally, seven studies were selected [ 16 , 17 , 18 , 19 , 20 , 21 ]. A total of 255 overweight and obese individuals were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Current findings did not show statistically significant changes in other lipid profiles, including total cholesterol, LDL, and HDL. More studies are needed since other findings from previous studies were controversial [ 17 , 19 , 20 ]. While our findings regarding lipid profiles did not show statistically significant changes, a previous study reported a significantly decreased lipid profile.…”
Section: Discussionmentioning
confidence: 99%